LANGUAGE SHIFT IN COMMUNICATION BY THE COMMUNITY OF LAIKANG VILLAGE IN TAKALAR DISTRICT - Anita CandraDewi; Ninik Rahayu Ashadi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Language contact that occurs in multilingual society causes various linguistic events. One of these linguistic events is language shift. In this case a person or group of people leave the first language or common language and switch to using a second language. The study of language shift in the village community of Laikang Village, Takalar Regency aims to describe the form of community language use based on the age domain, namely children, adolescents, and adults. The type of research used is descriptive qualitative research. Based on the form of the use of the Makassar language and Indonesian language with data sources from the Laikang village community, Takalar district obtained by using the listening method, namely listening techniques, engaging conversations, free listening techniques, engaging conversations, recording techniques, and note-taking techniques as well as speaking or interviewing methods in cases the phenomenon of language shift resulted in the finding that the Makassar language which is the language of the Laikang village community experienced a language shift. Even though adults are able to use the Makassar language actively, they show the dominant use of Indonesian in the form of their use of the language. Adolescents, although able to understand the Makassar language, are not able to use the Makassar language actively, while the children are very difficult and even unable to use the Makassar language, another indication is the existence of the Indonesian language which has shifted the existence of the Makassar language.